Anthropogenic influence on Amazonian forests in pre‐history: An ecological perspective. (28th October 2015) - Bush, Mark B.; McMichael, Crystal H.; Piperno, Dolores R.; Silman, Miles R.; Barlow, Jos; Peres, Carlos A.; Power, Mitchell; Palace, Michael W.
Abstract: An important debate has been re‐invigorated by new data concerning the size and environmental impacts of human populations in the Amazon Basin during pre‐history. Here, we review the history of debates concerning pre‐historic human occupation of the Amazon Basin along with the presentation of empirical data from archaeological and palaeoecological research. The combined evidence suggests that human occupation and resulting influence on Amazonian ecosystems were heterogeneous on both regional and local scales. Pre‐historic occupation sites are more likely to have been located in forests with a pronounced dry season or in forests that are within 15 km of a river floodplain, rather than in ever‐wet forests or in interfluvial regions far removed from large rivers. Forest enrichment of preferred species and game depletion through hunting are most probable within 15 km of an occupation site. Given the spatial and temporal patterning of these data, views of significant Amazonian‐wide cultural impacts on riverine and interfluvial forest are not supported at this time.